Distribution of volatile organic compounds (VOCs) in the urban atmosphere of Hangzhou, East China: Temporal variation, source attribution, and impact on the secondary formations of ozone and aerosol - Wang, Xin; Han, Yu; Tu, Xiang; Shen, Jiandong; Zhang, Baojun; Fu, Hongbo (Frontiers in Environmental Science, 2024)
Volatile organic compounds (VOCs) significantly influence air quality, atmospheric chemistry, and human health. An observational study was performed at the urban site of Hangzhou, China, to analyze VOC characteristics, sources, chemical reactivities, and their impact on ozone (O3) and secondary organic aerosol (SOA) formation throughout the year 2021. During the observation period, alkanes (40.13 %) emerging as the predominant VOC species. Seasonal variation in VOCs followed the order of winter (26.49 ppb) > spring (23.63 ppb) > summer (23.62 ppb) > autumn (20.47 ppb). The results of positive matrix factorization (PMF) revealed that solvent usage, combustion, and vehicle exhaust were the dominant VOC sources. Regional transport from nearby provinces also significantly contributed to VOC levels. These contributions varied seasonally, with southeastern air masses prevailing in both spring and autumn, eastern air masses impacting summer, and northwestern air masses affecting winter. The campaign-averaged value of total hydroxyl (OH) radicals was 19.08 s-1 . NO2 accounted for the most significant contribution to the overall OH reactivity (39.11 %), followed by VOCs (28.72 %). Notable seasonal fluctuations in OH reactivity followed the order of winter (24.20 s-1 ) > spring (19.22 s-1 ) > autumn (18.07 s-1 ) > summer (14.86 s-1 ). The average ozone formation potential (OFP) for the measured VOCs was calculated as 75.54 ppb, with alkenes being the dominant contributor. The highest value was observed in spring (83.05 ppb), the lowest value was in autumn (60.43 ppb). The SOA formation potential, mainly contributed by the aromatics, was averaged as 2.92 μg m-3 . Additionally, the top four SOA-contributing species across four seasons were toluene, benzene, m-xylene, and ethylbenzene. VOC-PM2.5 sensitivity analysis showed that VOCs exhibited higher sensitivity to PM2.5 on clean level (PM2.5 < 35 μg m -3 ) than on level with heavy pollution. Alkenes, oxygenated volatile organic compounds (OVOCs) and aromatics played significant roles in the transformations of O3 and SOA in Hangzhou. Therefore, controlling the concentrations of these species is crucial for reducing complex atmospheric pollution in the region. Overall, this study compiles scientific evidence on pollution sources in Hangzhou, providing the government with valuable information.